Preparation process of high-resistance M-type hexagonal ferrite and prepared product
By adjusting the SiO2 content and sintering temperature and combining the ball milling method of zirconia ceramic balls, the problem of low resistance of M-type hexagonal ferrite is solved, and high resistance and excellent magnetic and dielectric properties are achieved.
Patent Information
- Application Number
- CN202411982536.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The resistance of existing M-type hexagonal ferrite is low, mainly because the bivalent iron ions around the oxygen ions lose electrons to form oxygen vacancies and iron positive ions, resulting in current conduction and interface and grain boundary defect scattering, which reduces the resistance.
By adjusting the SiO2 content and sintering temperature in the auxiliary material, SiO2 is used as a flux to reduce the sintering temperature, and the degree of densification is controlled to improve the resistance. At the same time, zirconia ceramic balls are used for ball milling to reduce the entry of Fe2+ and regulate the magnetic structure and electrical characteristics.
The preparation of high-resistance M-type hexagonal ferrite is achieved, with a resistance greater than 21MΩ, and both magnetic and dielectric properties are improved, meeting the requirements of Br390-420mT, Hcb 270-300KA/m, Hcj 280-330KA/m and (BH)max31-33 kJ/m3.
Smart Images

Figure CN119751041A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of permanent ferrites, and more specifically, relates to a preparation process of high-resistance M-type hexagonal ferrite and the prepared product. Background Art
[0002] M-type ferrite has a large coercive force, high saturation magnetization and good chemical stability, and is widely used in permanent magnetic materials. However, the existing M-type hexagonal ferrite has a low resistance, which is mainly due to the divalent iron ions located around the oxygen ions. These ions lose electrons due to the lack of oxygen ions, forming oxygen vacancies and iron cations, which are charged through conduction, thereby forming current in the material, resulting in a decrease in resistance. In addition, there are interface and grain boundary defects in multiphase ferrite, which effectively scatter electron transmission, causing its resistance to further decrease.
[0003] Patent CN107056270A discloses a hexagonal sintered permanent ferrite magnet and a preparation method thereof. The composition formula of the hexagonal sintered permanent ferrite magnet of the invention is A 2+ 1-x-y B 1+ y La 3+ x Fe 3+ n-z Co 2+ z O 2- 19 Indicates that A is at least one of the divalent alkaline earth metals calcium, strontium, and barium, B is at least one of the monovalent alkali metals lithium, sodium, and potassium, and x, y, z, and n are the addition ratios of the elements, wherein x is 0.24-0.45, y is 0.03-0.10, z is 0.20-0.33, and n is 10.0-12.0, and 1.1z≤x≤1.8z, y+z≤x. The mixing of ingredients also includes one or a mixture of primary additives of silicon dioxide, boric acid, alkali metal chloride, and alkaline earth metal chloride, and the addition ratio is: silicon dioxide 0.05-0.5wt%. Monovalent alkali metals lithium, sodium, potassium, and alkaline earth metal chlorides are added in this patent. Alkali metal chlorides will produce HCl and other substances that are extremely corrosive to equipment during the high-temperature sintering stage, which will cause certain environmental pollution.
[0004] Patent CN102701721A discloses a low-cost sintered calcium permanent magnet ferrite and a preparation method thereof. The sintered calcium permanent magnet ferrite includes a hexagonal M-type ferrite main phase containing calcium, lanthanum, iron and zinc, and has the following characteristic molecular formula: Ca 1-x La x Fe 2n-z Zn z O 19; Wherein, x, z, n represent the molar ratio of calcium, lanthanum, iron and zinc, and x is 0.2-0.6, z is 0.2-0.4, n is 4-6, and x / z is 1.0-3.0. The secondary additives include calcium carbonate powder, silicon oxide powder, aluminum oxide powder, and boric acid powder. The addition amount of the secondary additives is: CaCO3: 0.3-1.5wt%, SiO2: 0.1-1.0wt%, Al2O3: 0.1-1.5wt%, H3BO3: 0.05-0.2wt%, and the sintering temperature is 1150℃-1250℃. However, the metal elements of lanthanum and zinc are added in this patent, resulting in excessive grain boundaries, affecting the density of ferrite, and then affecting the resistance of ferrite.
[0005] Patent CN117658645A discloses a method for removing silicon impurities from high silicon iron red for permanent ferrite, wherein the additive is strontium carbonate, one or a mixture of silicon dioxide, aluminum oxide, calcium carbonate, and boric acid, the sintering temperature is 1220-1270°C, and the holding time is 1-2 hours. The excessive Si content in the patent leads to strong conductivity and low resistance of the ferrite. Summary of the invention
[0006] 1. Problem to be solved
[0007] Aiming at the problem of low resistance of existing M-type hexagonal ferrite, the present invention provides a method for preparing high-resistance M-type hexagonal ferrite. The M-type hexagonal ferrite prepared by the method has higher resistance.
[0008] 2. Technical solution
[0009] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0010] The present invention provides a method for preparing high-resistance M-type hexagonal ferrite, which specifically comprises the steps of:
[0011] Step a, batching: pre-burned material and auxiliary materials in a certain weight ratio are batched in proportion, wherein the pre-burned material comprises, by mass percentage: Fe2O3 90.0%-92.2%, SiO2 0.126%-0.152%, Al2O3 0.094%-0.108%, CaO 0.056%-0.075%, SrO 7.5%-9.5%, and the rest are inevitable impurities;
[0012] The auxiliary materials include SiO2 0.05%-0.2%, CaCO3 0.5%, Al2O3 0.14%, HBO3 0.3% according to the mass percentage of the pre-sintered material;
[0013] Step b, ball milling: Add the ingredients in step a and water in a weight ratio of 1: (1.2-1.5) into a ball mill, mix, and ball mill for 10-12 hours;
[0014] Step c, sintering: sinter the ball-milled mixture obtained in step b at 1175° C.-1235° C. for 2 hours.
[0015] It should be noted that the presence of Si crystals in ferrite is equivalent to the presence of semiconductors. Under the action of an external electric field, the two carriers, electrons and holes, in semiconductor materials move in opposite directions. Therefore, this application reduces the transition of electrons and reduces its conductivity by reducing the content of SiO2. When the SiO2 content is lower than 0.2%, the resistance of the ferrite is significantly improved. Furthermore, SiO2 is a flux in M-type hexagonal ferrite, which can effectively reduce the sintering temperature. At a lower sintering temperature, it can effectively inhibit grain growth and refine grain particles; improve magnetic properties, increase magnetic permeability and saturation magnetization, and improve dielectric properties.
[0016] Among the auxiliary materials of this component and ratio, SiO2 is a flux. During the reaction, it can reduce the reaction temperature from 1300℃ to 1175℃~1230℃ by fluxing ferrite grains; CaCO3 mainly provides Ca 2+ , Ca 2+ Substituting Fe in the ferrite lattice 2+ and Co 2+ , effectively improve the residual magnetic properties; Al2O3 mainly provides Al 3+ , replacing Fe in the ferrite lattice 3+ and La 3+ , effectively improving the intrinsic coercive force performance; HBO3 is a dispersant, which reduces particle agglomeration and makes ball milling more uniform. The particle size after ball milling is more uniform, and the particle size is concentrated in the range of 0.75 to 0.85 microns.
[0017] Furthermore, the sintering temperature is controlled at 1175℃-1235℃. The sintering temperature is related to the densification degree of ferrite, which in turn affects the resistance. As shown in Table 1, when the sintering temperature is lower than 1175℃, the resistance of ferrite remains basically unchanged as the temperature increases. When the temperature reaches 1175℃, the resistance increases significantly, and as the temperature increases, the resistance continues to increase. The reason is that as the liquid phase of the additive flows, the densification proceeds rapidly, and the densification change first increases and then decreases. When the temperature reaches 1235℃, the density change rate reaches the highest, and the resistance is relatively high. When the temperature exceeds 1235℃, the grains grow excessively, the crystallization is serious, the density change rate decreases, and the resistance drops sharply.
[0018] Table 1 Density and resistance of ferrite at different sintering temperatures
[0019]
[0020] Furthermore, the ball milling medium in step c is zirconia ceramic balls, which are used instead of steel balls; zirconia balls are non-magnetic and have electrical insulation properties, which can reduce Fe 2+ The entry of Fe 2+ The presence of will reduce the resistance, prevent friction electrification, and reduce the generation and accumulation of electrons. In addition, during the ball milling process, the Zr in the zirconia ceramic ball 4+ Ion doping of M-type hexagonal ferrite at the B site can not only regulate the magnetic structure and magnetic properties of the material, but also 4+ Unequal doping of ions at the B position of hexagonal ferrite can also produce related defects, carriers and variable valence Fe ions, thereby changing the electrical properties of the material. It should be noted that zirconia ceramic balls, as ball milling media, will have losses during the ball milling process and enter the raw materials. The length of ball milling time will affect the Zr 4+ The longer the ball milling time, the more Zr 4+ The higher the ion doping amount, the shorter the ball milling time. 4+ The lower the ion doping amount, the 4+ When the ion doping amount is less than 0.06%, it is easier to replace the Fe in the upper spin lattice. 3+ ions, whose magnetization intensity decreases with the increase of Zr doping amount; 4+ As the ion doping amount increases, the Fe 3+ The ions will also be gradually replaced, and at this time, the saturation magnetization increases with the increase of doping amount.
[0021] Therefore, the present invention improves the resistance of M-type hexagonal ferrite by changing the content of SiO2 in the auxiliary material and selecting the sintering temperature according to the densification degree of the ferrite. The high-resistance M-type hexagonal ferrite finally obtained has the following properties: Br390-420mT, Hcb 270-300KA / m, Hcj 280-330KA / m, (BH) max 31-33 kJ / m 3 , resistance is greater than 21MΩ.
[0022] 3. Beneficial effects
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention controls the content of SiO2 in the auxiliary material so that it acts as a flux, reduces the sintering temperature, and controls the sintering temperature so that when the density change rate reaches the highest, the resistance is relatively high, which can effectively improve the magnetic properties, increase the magnetic permeability and saturation magnetization, and improve the dielectric properties;
[0025] (2) The present invention uses zirconium oxide ceramic balls instead of steel balls in the ball milling process. 4+ Ion doping of M-type hexagonal ferrite at the B site can not only regulate the magnetic structure and magnetic properties of the material, but also 4+ Unequal doping of ions at the B site of hexagonal ferrite can also produce related defects, carriers and variable-valence Fe ions, thereby changing its electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments, but it should be understood that these drawings are designed only for explanation purposes and are not intended to limit the scope of the present invention. In addition, unless otherwise specified, these drawings are intended only to conceptually illustrate the structural configurations described herein and are not necessarily drawn to scale.
[0027] Figure 1 This is a scanning electron microscope image of the high resistance M-type hexagonal ferrite of Example 1. DETAILED DESCRIPTION
[0028] The following detailed description of exemplary embodiments of the present invention refers to the accompanying drawings, which form a part of the description, and in which exemplary embodiments of the present invention that can be implemented are shown as examples. Although these exemplary embodiments are described in sufficient detail to enable those skilled in the art to implement the present invention, it should be understood that other embodiments can be implemented and various changes can be made to the present invention without departing from the spirit and scope of the present invention. The following more detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but is only for the purpose of illustrating and not limiting the description of the characteristics and features of the present invention, so as to propose the best mode for performing the present invention and to enable those skilled in the art to implement the present invention. Therefore, the scope of the present invention is limited only by the appended claims.
[0029] It should be understood that the following text is only used to describe one or several specific embodiments of the present invention, and does not strictly limit the scope of protection of the specific claims of the present invention. As used herein, the terms "parallel" and "perpendicular" are not limited to their strict geometric definitions, but include tolerances for reasonable and inconsistent machining or human errors.
[0030] The components and contents of the auxiliary materials in the examples of the present invention and the comparative examples are shown in Table 2.
[0031] Table 2 Composition and content of auxiliary materials in the embodiments of the present invention and comparative examples
[0032]
[0033] Example 1
[0034] A method for preparing high-resistance M-type hexagonal ferrite, which specifically comprises the steps of:
[0035] Step a, batching: pre-sintered materials and auxiliary materials are batched in proportion, wherein the components of the pre-sintered materials include by weight percentage: Fe2O3 90.25%; SiO2 0.142%; Al2O3 0.098%; CaO 0.069%; MgO 0.004%; MnO0.353%; SO3<0.005%; P2O5 0.005%; K2O<0.005%; Na2O 0.014%; V2O5<0.005%; TiO2<0.005%; CuO0.020%; ZnO<0.005%; Cr2O3 0.029%; NiO<0.005%; BaO 0.124%; SrO8.89%;
[0036] The auxiliary materials include SiO2 0.1wt%, CaCO3 0.5wt%, Al2O3 0.14wt%, H3BO3 0.3wt%, La2O3 0.4wt%, and Co2O3 0.2wt% by weight;
[0037] Step b, ball milling: the pre-sintered material and auxiliary materials in step a are placed in a ball mill with water and ball milled for 11 hours, wherein the weight ratio of the pre-sintered material and auxiliary materials to water is 1:1.2; the ball milling medium is zirconia ceramic balls;
[0038] Step c, sintering: after discharging and filtering the water, the slurry is pressed into round cake blanks in a press, and then put into a roller kiln for sintering at a sintering temperature of 1216°C.
[0039] After sintering, the ferrite sintered product is taken out, both sides are ground smooth and then dried to obtain permanent ferrite.
[0040] After placing the ferrite on a voltage withstand tester to test the breakdown voltage, the magnetic properties are tested.
[0041] The scanning electron microscope image of the obtained high resistance M-type hexagonal ferrite is as follows: Figure 1 As shown in Table 2, the performance meets the following requirements: Br412.3mT, Hcb 283KA / m, Hcj 296.4KA / m, (BH) max 31.2kJ / m 3 .
[0042] Example 2
[0043] The preparation method and process of the high resistance M-type hexagonal ferrite of Example 2 are basically the same as those of Example 1, except that the content of SiO2 in the auxiliary material is 0.05wt%.
[0044] The properties of the obtained high resistance M-type hexagonal ferrite are shown in Table 2, which meet the following requirements: Br 418.7mT, Hcb 275.1KA / m, Hcj 283.5.4KA / m, (BH) max 32.9kJ / m 3 .
[0045] Example 3
[0046] The preparation method and process of the high resistance M-type hexagonal ferrite of Example 3 are basically the same as those of Example 1, except that the content of SiO2 in the auxiliary material is 0.2%.
[0047] The properties of the obtained high resistance M-type hexagonal ferrite are shown in Table 2, which meet the following requirements: Br 406.2mT, Hcb 293.2KA / m, Hcj 306.1KA / m, (BH) max 32.6kJ / m 3 .
[0048] Example 4
[0049] The preparation method and process of the high resistance M-type hexagonal ferrite of Example 4 are basically the same as those of Example 3, except that the secondary sintering temperature is 1195°C.
[0050] The properties of the obtained high resistance M-type hexagonal ferrite are shown in Table 2, which meet the following requirements: Br 400.1mT, Hcb 295.2KA / m, Hcj 312.1KA / m, (BH) max 31.9kJ / m 3 .
[0051] Comparative Example 1
[0052] The preparation method and process of the M-type hexagonal ferrite of Comparative Example 1 are basically the same as those of Example 1, except that synthetic steel balls are used as the ball milling media.
[0053] The properties of the obtained high resistance M-type hexagonal ferrite are shown in Table 2, which meet the following requirements: Br 413.7mT, Hcb 286.5KA / m, Hcj 299.7KA / m, (BH) max 32.1kJ / m 3 .
[0054] Comparative Example 2
[0055] The preparation method and process of the M-type hexagonal ferrite of Comparative Example 2 are basically the same as those of Example 1, except that the content of SiO2 in the auxiliary material is 0.3%.
[0056] The properties of the obtained high resistance M-type hexagonal ferrite are shown in Table 2, which meet the following requirements: Br 403.8mT, Hcb 297.2KA / m, Hcj 312.4KA / m, (BH) max 33.7kJ / m 3 .
[0057] Comparative Example 3
[0058] The preparation method and process of the M-type hexagonal ferrite of Comparative Example 3 are basically the same as those of Example 1, except that the content of SiO2 in the auxiliary material is 0.25%, and the ball milling medium uses synthetic steel balls.
[0059] The properties of the obtained high resistance M-type hexagonal ferrite are shown in Table 3, which meet the following requirements: Br 405.3mT, Hcb 281.2KA / m, Hcj 302.3KA / m, (BH) max 33.5kJ / m 3 .
[0060] Table 3 Performance parameters of M-type hexagonal ferrite in the embodiments of the present invention and the comparative examples
[0061]
[0062] The present application improves the resistance of M-type hexagonal ferrite by changing auxiliary materials and ball milling methods.
[0063] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.
[0064] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.
Claims
1. A process for preparing high resistance M-type hexagonal ferrite, characterized in that: Includes steps: Step a, batching: pre-sintered material and auxiliary materials are batched in proportion, wherein the auxiliary materials include SiO2 0.05%-0.2%, CaCO3 0.5%, Al2O3 0.14%, HBO3 0.3%, La2O3 0.4%, Co2O3 0.2% by mass percentage of the pre-sintered material; Step b, ball milling: adding water to the ingredients in step a and then ball milling; Step c, sintering: sinter the mixture obtained after secondary ball milling in step b at 1175° C. to 1230° C. for 2 hours.
2. The preparation process according to claim 1, characterized in that: The pre-sintered material comprises: Fe2O3 90.0%-92.2%, SiO2 0.126%-0.152%, Al2O3 0.094%-0.108%, CaO 0.056%-0.075%, SrO 7.5%-9.5%, and the rest are inevitable impurities.
3. The preparation process according to claim 1, characterized in that: In step b, the ball milling medium is zirconia ceramic balls.
4. The preparation process according to claim 3, characterized in that: In step b, the ball milling time is 10 to 12 hours.
5. The preparation process according to claim 4, characterized in that: In step b, the mass ratio between the ingredients and water is 1:(1.2-1.5).
6. The product obtained by the preparation process according to any one of claims 1 to 5, characterized in that: The resistance of the obtained high resistance M-type hexagonal ferrite is greater than 21MΩ.
7. The product according to claim 6, characterized in that The high resistance M-type hexagonal ferrite meets Br390-420mT, Hcb 270-300KA / m, Hcj 240-380KA / m, (BH) max 31-33 kJ / m 3 .
8. The product according to claim 7, characterized in that The density of the high resistance M-type hexagonal ferrite is 5.10-5.20 g / cm 3 .
Citation Information
Patent Citations
Preparation method of permanent-magnet ferrite material
CN107293398A
Preparation method of economical permanent magnetic ferrite material
CN110963794A
Permanent magnetic ferrite material and preparation method thereof
CN111704452A
Normal-temperature high-standard soft magnetic ferrite material and preparation method thereof
CN113185276A
High intrinsic coercive force permanent magnet strontium ferrite and preparation method thereof
CN114105628A